Penerapan Perawatan dan Service Sepeda Motor Bagi Siswa SMK Ma’arif Nu Talang - Mukhamad Khumaidi Usman; Faqih Fatkhurozak; AMIN Amin nur akhmadi (CV. Multi Kreasi Media, 2022)
Abstract - The purpose of community service (PKM) is to practice the Tri Dharma of Higher Education for D-3 Mechanical Engineering lecturers, providing knowledge of understanding of motorcycle maintenance and service. The activity was carried out at SMK Ma'arif Nu Talang, Talang District, Tegal Regency, going according to plan, providing an understanding of how the 4-stroke motorcycle engine works. The hope of this activity is that students majoring in light vehicle engineering focus more on the competencies obtained during the training